RESHAPING THE WORLD, RETHINKING ACTORS: THE ROLE OF SUB-STATE ACTORS IN FOREIGN RELATIONS - Inass Abdulsada Ali (Journal of International Studies)
International relations scholars have increasingly debated the evolving landscape of actors that challenge the traditional state-centric world order. A key element of this transformation is the rise of sub-state actors, which engages in alternative diplomacy parallel to the state, transcending traditional state-centric frameworks. This paper explores the significant shifts in international actorness over the late 20th century, focusing on the emergence and implications of sub-state diplomacy, or "paradiplomacy." First, the study introduces sub-state actors and their role in challenging the dominant state-centric discourse. It then examines the dynamic evolution of paradiplomacy, highlighting how sub-states have expanded their global engagement, the opportunities this presents, and the potential threats it poses. Through a multi-scalar analysis, the paper critically assesses paradiplomacy's impact on long-held beliefs about regions, states, actors, and the international political system. Furthermore, the study shows how states can leverage their sub-national entities to deal with problems that threaten their sovereignty and global standing. The findings suggest that both the state and sub-state actors can engage in ambitious international activities, fostering greater global cooperation within the complexities of modern governance and competition.